DASAR PERTIMBANGAN MAJELIS HAKIM DALAM MEMUTUS PERKARA TINDAK PIDANA KORUPSI SECARA BERSAMA DAN BERLANJUT (STUDI KASUS PUTUSAN NOMOR 97/PID.SUS-TPK/2019/PN JKT.PST) - Agus Marsinta; Agnes Harvelian (Universitas Swadaya Gunung Jati, 2022)
Recently, corruption has been increasingly discussed, both in print and electronic media, as well as in seminars, workshops, discussions, and so on. Corruption has become a serious problem for the Indonesian people, because corruption in Indonesia occurs systemically, massively and structured so that it is not only detrimental to the state's financial condition, but also violates the social and economic rights of the community at large. The research method used is a normative research method that focuses on library research to obtain secondary data from legal materials. The normative approach is carried out by reviewing the provisions or applicable laws and regulations. The results of the study indicate that the provisions regarding criminal acts of corruption in Indonesia are regulated in Law no. 31 of 1999 concerning the Eradication of Corruption Crimes and Law no. 20 of 2001 concerning Amendments to Law no. 31 of 1999 concerning the Eradication of Corruption Crimes. In the consideration of the Panel of Judges, that in the public's view - the Defendant's actions were a disgraceful act, and during the examination process at the trial the Tribunal did not obtain justifying facts which could erase the unlawful nature of the Defendant's actions, nor the facts of forgiving reasons which could erase the guilt of the Defendant. Therefore, the defendant must be held accountable for his actions.